Mixed-ligand copper(ii) Schiff base complexes: the role of the co-ligand in DNA binding, DNA cleavage, protein binding and cytotoxicity. Issue 22 (10th May 2016) - Lian, Wen-Jing; Wang, Xin-Tian; Xie, Cheng-Zhi; Tian, He; Song, Xue-Qing; Pan, He-Ting; Qiao, Xin; Xu, Jing-Yuan
Abstract : Four novel mixed-ligand copper(ii ) Schiff base complexes were synthesized and characterized. The biological features of the complexes and how acetic auxiliary ligands manipulate these features were investigated. Abstract : Four novel mononuclear Schiff base copper(ii ) complexes, namely, [Cu(L)(OAc)]·H2 O (1 ), [Cu(HL)(C2 O4 )(EtOH)]·EtOH (2 ), [Cu(L)(Bza)] (3 ) and [Cu(L)(Sal)] (4 ) (HL = 1-(((2-((2-hydroxypropyl)amino)ethyl)imino)methyl)naphthalene-2-ol), Bza = benzoic acid, Sal = salicylic acid), were synthesized and characterized by X-ray crystallography, elemental analysis and infrared spectroscopy. Single-crystal diffraction analysis revealed that all the complexes were mononuclear molecules, in which the Schiff base ligand exhibited different coordination modes and conformations. The N–H⋯O and O–H⋯O inter- and intramolecular hydrogen bonding interactions linked these molecules into multidimensional networks. Their interactions with calf thymus DNA (CT-DNA) were investigated by UV-visible and fluorescence spectrometry, as well as by viscosity measurements. The magnitude of the K app values of the four complexes was 10 5, indicating a moderate intercalative binding mode between the complexes and DNA. Electrophoresis results showed that all these complexes induced double strand breaks of pUC19 plasmid DNA in the presence of H2 O2 through an oxidative pathway. In addition, the fluorescence spectrum of human serum albumin (HSA) with the complexes suggested that the quenching mechanism of HSA by the complexes was a static process. Moreover, the antiproliferative activity of the four complexes against HeLa (human cervical carcinoma) and HepG-2 (human liver hepatocellular carcinoma) cells evaluated by colorimetric cell proliferation assay and clonogenic assay revealed that all four complexes had improved cytotoxicity against cancer cells. Inspiringly, complex4, with salicylic acid as the auxiliary ligand, displayed a stronger anticancer activity, suggesting that a synergistic effect of the Schiff base complex and the nonsteroidal anti-inflammatory drug may be involved in the cell killing process. The biological features of mixed-ligand copper(ii ) Schiff base complexes and how acetic auxiliary ligands manipulate these features are also discussed.